Brick or Click? Channel Choice Disruptions in Travel Industry. (March 2019) - Jasrotia, Sahil Singh; Mishra, H. G.; Koul, Surabhi
In the current era of digital infusion, customer behaviour is highly fluctuating. This has resulted retailers to be in a confused situation. The current need of the situation is to understand this change in customer behaviour and strategise accordingly. The purpose of the current study is to investigate the drivers of the channel choice, in relevance to travel industry. The study presents a conceptual model that reflects the antecedents to customer channel choice in travel industry. The article is based on a qualitative research analysis using semi-structured interviews to systematically collect and analyse the data. A sample of 25 retailers and 27 customers were selected and interviewed. A grounded theory approach has been adopted to generate a conceptual model. The article identifies several antecedents to channel choice in travel industry. Factors such as customer awareness, urgency of purchase, promotions and facilities have been highlighted and elaborated through the three-staged coding process. The other antecedents of the channel choice that have been highlighted through the verbatim are catchment area, family influences and affordability. In travel industry, channel structures have been well-studied. These studies dominantly focus on the players of the channel or the role of the middleman. The current study is unique in the way it explores the channel choice of customers after understanding both the extremes of the channel, that is, retailers and the customers. Also the methodology used is unique in its own way.